Characterization of a PLLA-Collagen I Blend Nanofiber Scaffold with Respect to Growth and Osteogenic Differentiation of Human Mesenchymal Stem Cells - Markus D. Schofer; Ulrich Boudriot; Irini Leifeld; Romina I. Sütterlin; Markus Rudisile; Joachim H. Wendorff; Andreas Greiner; Jürgen R. J. Paletta; Susanne Fuchs-Winkelmann (The Scientific World Journal)
The aim of this study was to enhance synthetic poly(L-lactic acid) (PLLA) nanofibers by blending with collagen I (COLI) in order to improve their ability to promote growth and osteogenic differentiation of stem cells in vitro. Fiber matrices composed of PLLA and COLI in different ratios were characterized with respect to their morphology, as well as their ability to promote growth of human mesenchymal stem cells (hMSC) over a period of 22 days. Furthermore, the course of differentiation was analyzed by gene expression of alkaline phosphatase (ALP), osteocalcin (OC), and COLI. The PLLA-COLI blend nanofibers presented themselves with a relatively smooth surface. They were more hydrophilic as compared to PLLA nanofibers alone and formed a gel-like structure with a stable nanofiber backbone when incubated in aqueous solutions. We examined nanofibers composed of different PLLA and COLI ratios. A composition of 4:1 ratio of PLLA:COLI showed the best results. When hMSC were cultured on the PLLA-COLI nanofiber blend, growth as well as osteoblast differentiation (determined as gene expression of ALP, OC, and COLI) was enhanced when compared to PLLA nanofibers alone. Therefore, the blending of PLLA with COLI might be a suitable tool to enhance PLLA nanofibers with respect to bone tissue engineering.